2007
DOI: 10.1158/1078-0432.ccr-07-0463
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Inactivation of IκB Kinase-α in Oral Carcinomas and Tumor Progression

Abstract: Purpose: The loss of epithelial phenotypes in the process of carcinoma progression correlates with clinical outcome, and genetic/epigenetic changes accumulate aggressive clones toward uncurable disease. InB kinase-a (IKKa) has a decisive role in the development of the skin and establishes keratinocyte phenotypes.We assessed clinical implications of IKKa expression in oral carcinomas and epigenetic aberrations for the loss of expression. Experimental Design: We examined IKKa expression in oral carcinomas by imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
65
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(70 citation statements)
references
References 44 publications
2
65
0
3
Order By: Relevance
“…Here, we have exploited the marked reduction in IKK␣ expression and failure to shuttle to the nucleus exhibited in poorly differentiated human SCCs, combined with gene profiling, to unveil an explanation for the previously documented tumor-suppressive function of IKK␣ (15,16). We provide evidence for a role for IKK␣ in regulation of TGF-␤-activated cytostatic responses in keratinocytes, and have translated these observations to human tumor cell models to explain how IKK␣ acts as a tumor suppressor in SCC derived from stratified epithelia.…”
Section: The Tumor Suppressor Activity Of Ikk␣ Is Dependent On Its Numentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we have exploited the marked reduction in IKK␣ expression and failure to shuttle to the nucleus exhibited in poorly differentiated human SCCs, combined with gene profiling, to unveil an explanation for the previously documented tumor-suppressive function of IKK␣ (15,16). We provide evidence for a role for IKK␣ in regulation of TGF-␤-activated cytostatic responses in keratinocytes, and have translated these observations to human tumor cell models to explain how IKK␣ acts as a tumor suppressor in SCC derived from stratified epithelia.…”
Section: The Tumor Suppressor Activity Of Ikk␣ Is Dependent On Its Numentioning
confidence: 99%
“…A tumor-suppressive role for IKK␣ in SCC was recently identified in a mouse model of chemically induced SCC and a small number of human samples (15). More recent evaluation of IKK␣ expression in SCC revealed its loss in about 30% of such cancers, especially in those that develop a highly invasive phenotype (16). It is not clear, however, how IKK␣ exerts its tumor-suppressive activity in human SCC, and different possible modes of action were recently discussed (17).…”
mentioning
confidence: 99%
“…[7,9,10] Alternatively, IKKα suppresses carcinogenesis in the skin, lungs, esophagi, nasopharynges, and pancreas of humans and mice independently of canonical and noncanonical NF-kB pathways ( Figure 1B). [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28] These findings highlight the medical importance of IKK/NF-kB in the pathogenesis of human diseases and malignancies.…”
Section: Introductionmentioning
confidence: 84%
“…Severe autoimmunity and systemic autoinflammation Tumors in the esophagus and oral cavity/ fungal infection [25,35,36] Skin, lung, esophgeal, oral, and pancreatic cancer [15][16][17][18][19][20][21][22][23][24][25][26][27][28] www.advancedsciencenews.com www.bioessays-journal.com NF-kB pathways. [1,13,14,[48][49][50] The thymus of Ikkα À/À newborns show reduced medullary regions and mTEC numbers.…”
Section: Autoimmunity and Systemic Inflammationmentioning
confidence: 99%
“…Several laboratories have demonstrated that IKKa expression was downregulated, or that its localization was altered in human squamous cell carcinomas of the skin, lungs, and head and neck, [16][17][18][19][20] highlighting the importance of IKKa in human malignancy development. We showed that induced IKKa deletion in keratinocytes causes epidermal hyperplasia and spontaneous skin tumors.…”
mentioning
confidence: 99%